Seed demand and supply responses - Spielman, David J.; Mekonnen, Dawit Kelemework (International Food Policy Research Institute, 2018)
For centuries, efforts to improve, multiply, and distribute teff seed have relied on informal mechanisms, primarily farmers’ own selection of varieties exhibiting desirable yield, taste, color, or stress-resistance characteristics, and farmer-to-farmer exchanges of seed embodying these traits. It was not until the mid-20th century that Ethiopia—like many other developing countries—developed a system based on modern science to breed improved teff cultivars, distribute improve teff seed, and accelerate the contribution of genetic gain to teff yield growth across the country’s smallholder farming systems. Today, these informal mechanisms still account for up to 90 percent of seed supply, with the modern infrastructure accounting for the remainder (Bishaw, Sahlu, and Simane 2008; Sahlu, Simane, and Bishaw 2008). This suggests that there are challenges still to be overcome in enhancing teff productivity—in increasing output per area, maintaining yield gains from prior investments in research, reducing yield variability within and across seasons, and increasing tolerance and resistance to biotic and abiotic stresses. Part of Ethiopia’s challenge relates to the fact that teff is a neglected species (more pejoratively referred to as an “orphan crop”). Teff is not cultivated extensively in any other country and is thus not a destination for public investment in breeding. Teff is not a food security crop of global importance and is thus not a priority crop in the international agricultural research system— unlike rice, wheat, and maize. Teff is, in effect, unable to benefit from research spillovers from public investment in national (until recently) and international plant breeding programs, international exchanges of germplasm, and modern seed supply systems.